Physical properties of Physalis Peruviana L. - Oliveira, Solange (2015)
Physalis (Physalis Peruviana L), also known as Cape Gooseberry or Ground-cherry, plays an important role in nutrition being an excellent base for dietetic products. Highly valued for its unique ﬂavor, texture and color, recent research has shown that physalis is rich in many beneﬁcial compounds. In this study were evaluated some biometric characteristics of physalis, such as the diameter and mass, and which allowed calculating others, like: surface area, volume or density. Other physical properties were also evaluated, namely the color coordinates, by means of a Chroma metter, and textural parameters evaluated by a texturometer: ﬁrmness and elasticity. The physalis analyzed in the present work have an average diameter of 1.69 cm, a surface area of 8.98 cm2, a volume of 2.51 cm3, a mass of 2.77 g and a density of 1.10 g/cm3. The color coordinates were found to be 56.72 for lightness, 16.69 for redness and 58.11 for yellowness. Regarding texture, two attributes were evaluated, namely skin ﬁrmness and elasticity, and the average values found were 2.40 N and 2.94 mm, respectively. The results of this work are in accordance with data from literature reported by other authors.